High cell‐density cultivation of phenolic acid decarboxylase‐expressing Escherichia coli and 4‐vinylguaiacol bioproduction from ferulic acid by whole‐cell catalysis. Issue 8 (2nd March 2018) - Chen, Yuheng; Li, Lulu; Long, Liangkun; Ding, Shaojun
Abstract: BACKGROUND: 4‐vinyl guaiacol (4‐VG) is a high value‐added product widely used in the cosmetic, pharmaceutical, and chemical industries. The practical bioproduction of 4‐VG using phenolic acid decarboxylases has been limited by its relatively high biocatalyst cost and low yield and product concentration. RESULTS: In the present study, high‐cell density cultivation was employed to improve the activity and production of phenolic acid decarboxylase from Bacillus licheniformis (BLPAD) in recombinant Escherichia coli . The factors influencing enzyme production in E. coli such as the induction point and temperature for induction and feeding strategies were optimized. The highest BLPAD activity (531 U mL ‐1 ) and productivity (20.4 U mL ‐1 h ‐1 ), respectively, were achieved in a 5 L bioreactor using a glucose exponential feeding strategy with isopropyl β‐D‐thiogalactoside (IPTG) as inducer. Furthermore, a high BLPAD production level (512 U mL ‐1 ) was achieved using lactose as an inducer and continuous lactose feeding. Using a biphasic emulsion system with equal volumes (1 L) of cyclohexane as a organic solvent and a substrate fed‐batch strategy, the concentration and conversion yield of 4‐VG reached 129.9 g L ‐1 (85.6%) in a 5 L bioreactor by whole‐cell biocatalysis, which is the highest reported to date. CONCLUSION: This study describes a strategy for large‐scale 4‐VG bioproduction using the biocatalytic method. © 2018 Society of Chemical Industry